Studies on the preparation of transferrin-DNA conjugates and their interactions with cells - Strydom, Andreas Stefanus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Pharmacology)) -- University of Stellenbosch, 1992.